Quality of work life and employee efficiency in public and private hospitals in Kenya - Trinner Mukamba Mabele; Jesse Maina Kinyua; Joseph Kipyegon Bengat (Cogent Business & Management)
This study aimed to compare the influence of quality of work life on employee efficiency in public and private level 5 and 6 hospitals in Kenya. A cross-sectional descriptive research design and correlation research design were adopted. Primary data were collected, using structured questionnaires, from 370 respondents, from ten level 5 and two level 6 hospitals in Kenya. Descriptive and inferential statistics were used to analyze data. Hypothesis was tested at 5% significance level. The findings revealed a positive linear significant influence of quality of work life on employee efficiency in both public and private level 5 and 6 hospitals in Kenya. It was therefore concluded that enhancement of quality of work life results in improved employee efficiency in both public and private hospitals in Kenya. The study recommends that both public and private hospitals in Kenya enhance their quality of work life in terms of flexible working arrangements and opportunities for personal career growth in order to boost employee efficiency. The study makes substantial contributions to the existing literature on the quality of work life and employee performance, as well as provide useful input in policy formulation in hospitals.